Characterization of a Pt mirror to be used to deflect synchrotron radiation beam onto Langmuir monolayers - Vieira, Carlos, E. P. (2015)
A homemade mirror for X-rays has been built to prepare a diffraction beamline for liquid surface diffraction and scattering measurements. This simple approach is in operation at the XRD2 bending-magnet beamline at the Brazilian Synchrotron Light Laboratory.